Análise do desempenho e emissões de um motor de ignição por compressão utilizando várias proporções de biodiesel - Araújo, Ludmila Martins de (2019)
The internal combustion engines’ emissions, one of the biggest concern in modern days, particularly on the diesel ones, places a critical role since the design stage inside manufacturers’ headquarters. The search for practical solutions that can deliver substantial performance results is becoming an industry standard. The predictable oil shortage and the global environment awareness drive researchers to non-conventional energy sources and new – and less harmful for the Earth – combustion processes. Biodiesel presents itself as one possible solution for this equation for internal combustion engines (ICE), where its main quality is to avoid diesel’s critical problems. To achieve this results, tests have been made on a chassis roll dynamometer with a 2016 model year Chevrolet S10 LT truck on fully stock specifications, using common S10 diesel (that already contains 10% of biodiesel), B15 diesel (loaded with 15% biodiesel) and B100 diesel (pure biodiesel). To make sure if this alternative can fulfill the society’s needs and be used on current vehicles and light trucks, several parameters were measured, such as exhaust gas opacity, peak torque and power and greenhouse gases concentration. This study made possible the analysis of biodiesel’s effect on the engine, showing that this renewable energy source make substantial benefits performance-wise, being the reduction in gas opacity and NOx levels and a 7 whp increase the most notable achievements.